Pengembangan Model Pembelajaran Pendidikan Agama Islam (PAI) di Era Web 3.0: Inovasi, dan Tantangannya - Azhar, Dzul; Bahij, Muhammad Alfan; Hasan, Ismail; Budiyono, Slamet (TSAQOFAH, 2024)
In the era of Web 3.0, digital technology has transformed various aspects of life, including education, necessitating that Islamic Religious Education (PAI) adapts to remain relevant and effective. This article examines the development of PAI learning models that utilize digital technology to enhance the quality of education, by exploring fundamental PAI theories and the role of technology in education. The findings indicate that integrating technology into PAI can increase student engagement, enrich learning experiences, and facilitate a deeper understanding of the subject matter. However, there are still challenges in this innovative era that pose tasks for relevant stakeholders. In conclusion, developing adaptive and innovative PAI learning models is crucial to meet educational needs in the Web 3.0 era, with recommendations for further research and practical implementation to assist educators and policymakers in improving the quality of PAI education.